OPTIMAL STRATEGY FOR INDONESIAN SHARIA STOCKS: BACKTESTING BUY-HOLD, DCA, TRADING (2014-2024) - Darma, Hendra; Widodo, Slamet; Agustini, Rooswanti Putri Adi; Tutuko, Bambang; Kustyadji, Gatot; Sari, Anggi Tita (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study provides a comprehensive comparative analysis of three distinct investment strategies—Buy-and-Hold (B&H), Dollar-Cost Averaging (DCA), and an active trading model based on Moving Average Convergence Divergence (MACD) and Relative Strength Index (RSI) indicators—applied to the universe of Sharia-compliant stocks listed on the Jakarta Islamic Index (JII) in Indonesia. Utilizing a survivorship-bias-free methodology, this research conducts a rigorous backtesting simulation over an 11-year period from January 2014 to December 2024, with an initial capital of IDR 100 million. The quantitative analysis is uniquely integrated with a qualitative jurisprudential (fiqh) assessment, evaluating each strategy's adherence to core Islamic financial principles, particularly the prohibitions of excessive uncertainty (gharar) and speculation (maysir), and its alignment with the higher objective of wealth preservation (hifz al-mal). The empirical results indicate that while the Active Trading strategy generated the highest cumulative return, the passive Buy-and-Hold strategy achieved a superior risk-adjusted performance, evidenced by the highest Sharpe Ratio. The jurisprudential analysis reveals that passive strategies exhibit the highest degree of Sharia compliance, being free from concerns of speculation and ambiguity of ownership inherent in high-frequency trading. By synthesizing these dual perspectives, the study concludes that the Buy-and-Hold strategy represents the optimal approach for the Sharia-conscious investor in the Indonesian market, balancing robust financial performance with steadfast adherence to Islamic ethical principles. This research contributes to the literature by offering a long- term empirical test on a key emerging Islamic market and by bridging the gap between quantitative financial analysis and classical Islamic commercial jurisprudence.